Environmental management in sugar-energy sector: a comparative analysis - Andréia Marize Rodrigues (Revista Produção Online, 2014)
With the rise of the environmental variable in the business environment, companies started to give greater attention to strategies and practices focused on the rational use of natural resources and minimize the environmental impacts of their business operations. Many productive sectors stood out in the reflections on production and the environment, as is the case of the sugar energy industry, which constitutes a sector with a highly demanding industrial activity of natural resources, whether as sources of inputs as depositories of waste production. Thus, the aim of this paper is a comparative analysis of environmental practices of two sugar energy plants, both from the point of view of their operational strategy and regarding the suitability of the disposal of waste generated by the industrial area. It was concluded that, although many practices adopted by businesses are analogous, one of the studied plants have distinctive environmental performance, because of the increased attention given to the implementation of environmental practices and especially the inclusion of the environmental variable in their strategies.